Production of Oligosaccharides from Pine Nut Shells by Autohydrolysis - Torrado, Ivone (2023)
Pinus pinea nuts are commercial relevant Mediterranean edible forest nuts, with an increasing production and market value, whose industrial processing yields a lignocellulosic by-product, the pine nut shells, currently only used for combustion. Little research has been done on pine nut shells that could support a value-added application for this residue. This work studies for the first time the production of oligosaccharides by autohydrosis, and aims at an integrated upgrade within the biorefinery framework. Autohydrolysis was explored in the temperature range between 150 and 230 °C (corresponding to severity factors 2.13–4.63). Oligosaccharides, mainly xylo-oligosaccharides (95% of the total), were the key soluble products, reaching 28.7 g/100 g of xylan of the feedstock at the optimal conditions (log R 0 4.01). Other products were monosaccharides and phenolic compounds that reached 7.8 and 4.7 g/L, respectively, under the most severe conditions. The stability of the oligosaccharides at different temperatures (room, 37 °C and 100 °C) and pH (between 1 and 11) grant them significant market potential in the food and pharma sectors. The pre-treated pine nut shells by autohydrolysis presented an improved, although low, enzymatic digestibility (14%), and an improved high-heating value, therefore advising their further valorization by thermochemical pathways